Genetic Characteristics and Transcriptional Regulation of Sodium Channel Related Genes in Chinese Patients With Brugada Syndrome - Zhang, Ziguan; Chen, Hongwei; Chen, Wenbo; Zhang, Zhenghao; Li, Runjing; Xu, Jiajia; Yang, Cui; Chen, Minwei; Liu, Shixiao; Li, Yanling; Wang, TzungDau; Tu, Xin; et al. (Frontiers in Cardiovascular Medicine, 2021)
Abstract Objective: To investigate genetic characteristics and transcriptional regulation of gene SCN5A for Brugada syndrome (BrS) in China. Methods: Using PubMed, Medline, China National Knowledge Internet (CNKI) and Wanfang, Chinese patients with BrS who underwent SCN5A gene testing were studied. Results: 27 suitable studies involving Chinese BrS patients who underwent SCN5A gene test were included. Currently, the total number of SCN5A gene mutations/variations reported in Chinese BrS patients was 55 and the number of SCN5A gene mutations/variations in southern China was significantly lower than in northern China (10 vs. 45). According to mutations/variations location distribution, gene SCN5A mutations/variations of southern China mostly occurred in the regions of α-subunit of NaV1.5, including DIII (Domain III), DIV, DIII-DIV, C-terminus regions and 3'UTR region. Furthermore, we analysed the post-transcriptional modifications (PTMs) throughout the NaV1.5 encoded by SCN5A and found that the PTMs changed in 72.7% of BrS patients in southern China and 26.7% in Northern China. Conclusions: SCN5A mutation/variations of BrS patients in southern China mostly occurred in DIII-DIV to C-terminus region and the 3'-UTR region of SCN5A gene, which was significantly higher than that in northern China. Besides, the character of PTMs variation might involve in the regulation of the pathogenesis of BrS patients in southern China.